Agen Based Modeling for Corn Supply Chain Risks Identification and Sales Negotiation in PTPN VIII - Hidayat, Syarif; Suliandar, Dyah Ayu (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2020)
PTPN VIII is a state-owned company in West Java cultivating several kinds of commodities, and still have three marginal farmlands with a total size of 3000 hectares open for investment for corn. The type of corn that would be produced is corn feed for poultry needs. Three agents are involved in this agent-based model: the farmers (or cooperatives), PTPN VIII, and the buyers of the corn yields. All agents face risks in doing their businesses which hamper or reduce their probability of achieving their business goals. The potential risks are identified using fuzzy reasoning method. The three blocks of farmland have different levels of fertility. Farmers are expected to compete for the hunt of farmland to rent for cultivating corns, until their funds run out. They must prepare the land, procure their best corn seeds, plant and maintain the crops, and eventually harvest, dry and sell their corn yield. The dryness of the corn grains dictates the selling price. The buyers will buy the corns until their demands are fulfilled for the particular season. There will be a negotiation process between agents to reach an agreement. Each agent seeks to achieve its goal. This is why agent-based modelling is employed. Netlogo software is used to develop the model. Based on fuzzy reasoning method the obtained result shows that the most potential risk is quality risk. The negotiation results show that when both buyer and seller experience heightened degree of risk appetite, the shortest negotiations are achieved.